Unequal citizens: Cairo between gated and informal - Aly, Hend Ibrahim Muhammed (AUC Knowledge Fountain, 2017)
The conception of citizenship which accompanied the emergence of the nation-state, in essence, relates to ‘a territorially bounded population with a specific set of rights and duties.’ Such a conception of citizenship assumes that all the members of the nation have exactly the same set of rights and duties. I am interested in studying Cairo. Unfortunately, it is particularly far from this normative definition of citizenship, as its citizens are not equal. For that reason, I am keen on studying citizenship in practice, as a relation between citizens and state. I argue that state practices, represented in urban planning, are constructing distinct communities based on spatial segregation and inequality which constitute different citizenships within the same society. These different conceptions of citizenship imply that the citizens of the same nation have distinct visions on their roles as citizens and the role of the state towards them. Consequently, the state-society relations are framed differently by both the citizens and the state, based on the citizens’ discrete social, economic and political realities. I am specifically interested in answering the question of how does state-citizen relations differ from gated communities to informal areas? And what are the implications of these different conceptions of citizenship? In an attempt to answer this question, fieldwork has been conducted in two selected neighboring areas; Uptown Cairo representing a gated community and Manshīyat Nāṣir representing an informal area.